Analisis Potensi Kebangkrutan Dengan Mengunakan Model Springate S.Score : (Studi Kasus Pada Perusahaan Penerbangan Yang Terdaftar Di BEI)” - Elsa Pondi; Rati Pundissing; Mince Batara (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2023)
Analysis of Potential Bankruptcy Using the Springate S.Score Model (Case Study) in Aviation Companies Listed on the IDX.This research aims to determine financial distress in airline companies listed on the stock exchange. The type of data used is secondary data in the form of data in the form of documents obtained from the official BEI link (www.idx.co.id). The data analysis technique used is the Springate model. .score. The research results show the springate score analysis method. This is indicated by the Springate score being less or more than the predetermined score. in airline companies during 2018-2021, (1) PT Garuda Indonesia (Tbk) (2) PT Jaya Trishindo (Tbk) (3) PT MNC energy investment (Tbk) and (4) PT AirAsia (Tbk) experienced financial distress, and in 2022 it will also experience financial distress but PT Garuda Indonesia will not experience financial distress.